2013
DOI: 10.1037/2329-0382.1.s.3
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice, social stress, and mental health in lesbian, gay, and bisexual populations: Conceptual issues and research evidence.

Abstract: In this article the author reviews research evidence on the prevalence of mental disorders in lesbians, gay men, and bisexuals (LGBs) and shows, using meta-analyses, that LGBs have a higher prevalence of mental disorders than heterosexuals. The author offers a conceptual framework for understanding this excess in prevalence of disorder in terms of minority stress-explaining that stigma, prejudice, and discrimination create a hostile and stressful social environment that causes mental health problems. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

117
2,474
3
130

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,554 publications
(2,724 citation statements)
references
References 149 publications
(275 reference statements)
117
2,474
3
130
Order By: Relevance
“…Bisexual identity may be associated with unique stresses, multiple marginalization, and limited support. [52][53][54] Childhood sexual abuse also emerged as an important predictor of abuse; this is in line with previous studies, which found that women abused as children were twice as likely to experience violence as adults, 4 and may support the importance of early interventions. 55 There are several limitations to this study.…”
Section: Discussionsupporting
confidence: 83%
“…Bisexual identity may be associated with unique stresses, multiple marginalization, and limited support. [52][53][54] Childhood sexual abuse also emerged as an important predictor of abuse; this is in line with previous studies, which found that women abused as children were twice as likely to experience violence as adults, 4 and may support the importance of early interventions. 55 There are several limitations to this study.…”
Section: Discussionsupporting
confidence: 83%
“…The minority stress model described by Meyer [42] explains that stress which particular minority groups (such as lesbian, gay, bisexual and trans people) can experience are due to the relationship between minority and dominant values which results in conflicts with their social environment. This model suggests that stress in specific minority groups can largely be explained by stressors induced by a hostile, transphobic culture, which often results in a lifetime of harassment, abuse, victimization and discrimination [43]. This explains why levels of transphobia were predictive of psychopathology and were more common among the NSSI group.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, men indicated whether they were currently receiving treatment for depression or anxiety or both. Experiences related to stigma are closely linked with the mental health of gay men (Meyer, 2003). In addition to assessing mental health directly, we included five items for variables that tend to be stigma-related among gay men.…”
Section: Mental Health and Stigmamentioning
confidence: 99%